2015
DOI: 10.1111/jav.00536
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nest predators and weather on reproductive success and population limitation in a long‐distance migratory songbird

Abstract: Although avian nesting success is much studied, little is known about the relative importance of the factors that contribute to annual reproductive success and population limitation, especially for long-distance migratory songbird species. We combined a fi eld experiment limiting access to nests by mammalian predators with modeling of long-term fi eld data of American redstarts (Parulidae: Setophaga ruticilla ) to assess the eff ects of multiple environmental variables on breeding success and population limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 89 publications
(158 reference statements)
1
37
0
Order By: Relevance
“…For example, retrospective analyses have emphasised the importance of demographic rates related to breeding productivity or subadult return rate as drivers of population growth across a diverse range of species including seabirds (Ezard, Becker & Coulson ), songbirds (Sherry et al . ) and raptors (Carrete, Donázar & Margalida ). Previously, Harrison et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, retrospective analyses have emphasised the importance of demographic rates related to breeding productivity or subadult return rate as drivers of population growth across a diverse range of species including seabirds (Ezard, Becker & Coulson ), songbirds (Sherry et al . ) and raptors (Carrete, Donázar & Margalida ). Previously, Harrison et al .…”
Section: Discussionmentioning
confidence: 99%
“…These temporal patterns may result from changes in predator activity patterns or abundance. One factor that may cause annual variation in predator behavior is weather (Sperry and Weatherhead 2008, Cox et al 2013, Sherry et al 2015. Rat snakes increase activity as temperatures warm during the spring and early summer and this increased activity may be correlated with changes in seasonal nest success (Sperry et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that nest predation rates are relatively low (∼ 30%) in boreal forests relative to temperate forests (Darveau et al ), and predation pressure has been shown to decrease with latitude in other taxa (shorebirds, McKinnon et al ). Thus we considered it unlikely that predation pressure would limit population expansion into boreal Alaska, despite the strong role that predation plays in population dynamics of temperate forest birds (Sherry et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Four of the species for which our model predicts current Alaskan boreal occupancy have not been detected there, which is not surprising given the plethora of factors that may contribute to successful range expansion and detection, and the large stochastic component (Pielou 1991). For example, the absence of American redstart Setophaga ruticilla and warbling vireo Vireo gilvus may be explained by their strong association with deciduous habitats, particularly along riparian corridors (Sherry andHolmes 1997, Gardali andBallard 2000), which are largely discontinuous across the northwestern cordillera into boreal Alaska -but do connect with southeastern Alaska, where these species are found. Indeed, several other species -e.g.…”
Section: Perceived Barrier Weakmentioning
confidence: 99%